Effect of plant spacing and picking time on fruit quality of yellow passion fruit in Viamão, RS - Ritzinger, Rogério; Manica, Ivo; Riboldi, João (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was established at Viamão, RS, Brazil, with the objective of determining the effect of six plant spacings and two picking dates on fruit quality of yellow passion fruit (Passiflora edulis f. flavicarpa Deg.). The spaces in the rows were 2,00, 2,75, 3,50,4,25, 5,00 and 5,75 m, and 2,50 m between rows; plant density ranged from 695 to 2000 plants/ha. The fruits for analysis were collected on February 10 and May 19, during the production peaks in 1982. The spacing did not affect the quality of the fruit expressed by the content of peel, juice and seed with pulp residues, pH, total acidity, total soluble solids, reducing sugars and total soluble solids total acidity ratio. Differences in acidity, reducing sugars and total soluble solids acidity ratio between picking dates were observed due probably to climatic factors.